Authentic Leadership on Turnover Intention of Millenial Hotelier: Worklife Balance as Mediator - Indrayani, I Gusti Ayu Putu Wita (Jurnal Penelitian Pariwisata, 2022)
This research aims to explore the work-life balance of millennial hoteliers in the Sarbagita area (Denpasar, Badung, Gianyar, and Tabanan) and its role as a mediator in the relationship between authentic leadership and turnover intention. To answer the objectives of this study, multiple linear regression analysis techniques with the assistance of the SPSS version 28 program were applied. Data collection techniques were carried out by distributing questionnaires to 100 millennial employees and validated through interviews with the general managers of five-star hotels. The main finding of the current study was that work-life balance was not proven to mediate the effect of authentic leadership on the intention of turnover of the millennial hotelier. This study recommends that hotel management elaborates on a clear, transparent, directed, and structured work-life balance program for millennial employees who will dominate the workforce in the Society 5.0 era. The results of this study contribute practically to the decision-making of five-star hotel management in the Sarbagita area to retain the best talent of the millennial generation, which emphasizes the quality of human resources. Keywords: Work-Life Balance, Authentic Leadership, Turnover Intention, Hotel